Experimental sensorless control for IPMSM by using integral backstepping strategy and adaptive high gain observer. (February 2017) - Hamida, M.A.; de Leon, J.; Glumineau, A.
Abstract: In this paper a robust sensorless control for an Interior Permanent Magnet Synchronous Motor (IPMSM) is designed. The proposed control strategy uses a backstepping controller, whose robustness is improved by using integral actions added at each step of the original algorithm, and by a Maximum-Torque-Per-Ampere strategy (MTPA) to improve its energy efficient operation. Furthermore, to implement this controller in the framework of the mechanical sensorless control from the only measurements of the currents and voltages, an adaptive interconnected high gain observer is developed for estimating the rotor speed, the position and the load torque. Moreover, sufficient conditions are given to ensure the practical stability of the Observer-Controller system even if bounded uncertainties occur. Finally, the performance and the effectiveness of the designed method are tested experimentally throw a significant benchmark including different speed references and with significant robustness tests. A comparative evaluation of the computational effort of our scheme with respect to classical motor control is given.